2015
DOI: 10.1007/s40830-015-0011-6
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Arc Melting (PAM) and Corrosion Resistance of Pure NiTi Shape Memory Alloys

Abstract: Plasma arc melting (PAM) as a suitable noncontaminating melting route for manufacturing high-quality NiTi alloy was successfully examined. The corrosion resistance of PAM Nitinol was evaluated by both potentiodynamic and potentiostatic tests and compared with lower purity NiTi produced by vacuum induction melting (VIM). For the electro-polished surfaces, excellent corrosion resistance of NiTi comparable with the Ti alloys was found with no pitting up to 800 mV versus saturated calomel electrode in simulated bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 20 publications
2
12
1
Order By: Relevance
“…The early‐stage pits were similar in growth to those around oxidized carbide inclusions examined by Shabalovskaya et al The inclusions associated with pitting in the present work appeared to be Ti 2 NiO x (or Ti 4 Ni 2 O x ), which is consistent with other work showing that pitting can occur at Ti 2 Ni particles and on nitinol containing Ti 2 Ni and Ti 2 Ni x O y inclusions without any TiC inclusions …”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The early‐stage pits were similar in growth to those around oxidized carbide inclusions examined by Shabalovskaya et al The inclusions associated with pitting in the present work appeared to be Ti 2 NiO x (or Ti 4 Ni 2 O x ), which is consistent with other work showing that pitting can occur at Ti 2 Ni particles and on nitinol containing Ti 2 Ni and Ti 2 Ni x O y inclusions without any TiC inclusions …”
Section: Discussionsupporting
confidence: 91%
“…The preferential initiation of the secondary pits at larger inclusions provided further evidence that the susceptibility of EP nitinol to pitting corrosion is governed by the size of inclusions. Tuissi et al likewise found that the susceptibility to pitting corrosion of MP nitinol containing Ti 2 Ni and Ti 2 Ni x O y inclusions decreased with polishing particle size from 600‐grit to 1‐µm . The size of the larger inclusions (∼2–3 µm) in secondary pits was consistent with that of the larger inclusions (<5 µm) in the MP nitinol matrix.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…NiTi-based shape memory alloys have attracted great scientific and technological interests, due to their remarkable mechanical and chemical properties, such as superelasticity, shape memory behavior, good corrosion resistance [1,2], hydrogen storage ability, and good biocompatibility [3,4]; thereby they are very appropriate for biomedical and dentistry applications [5,6]. The observed shape memory effect in NiTi alloy is mainly caused by the existence of NiTi-austenite (B2) and NiTi-martensite (B19 ) phases [7].…”
Section: Introductionmentioning
confidence: 99%
“…The surface in the scratched area could in fact be quite different from that produced by a treatment such as electropolishing or passivation, particularly with regard to inclusions. Pitting appears to initiate at inclusions in EP nitinol and 316 stainless steel . Exposure to a higher concentration of possibly larger inclusions in the scratched area means that the value of E b obtained by the scratch method may not accurately reflect the pitting resistance of an alloy with a treated surface.…”
Section: Methodsmentioning
confidence: 99%